Pengaruh Persepsi Kegunaan Dan Kualitas Sistem Terhadap Niat Untuk Menggunakan Sistem Informasi Pendapatan - Rachmawati, Ira; Budiarti, Laeli (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2024)
This research aims to determine the influence of perceived usefulness and system quality on the intention to use the Revenue Information System. This research uses a quantitative approach with a survey method located in Unsoed. The population in this research is Revenue Treasurers, Revenue Treasurer Staff, and Revenue Information System operators. The sampling technique uses saturated sampling or census. The research data uses primary data in the form of respondents' answers to the statement items contained in the questionnaire. The research results show that perceptions of system usefulness and quality have a positive effect on intention to use the Revenue Information System. If the perceived usefulness and quality of the system increases, then the intention to use the Revenue Information System also increases. The implications of this research are for system owners to focus on perceptions of the usability and quality of the system through further training activities if there is development or addition of new features to the system, carrying out further evaluations regarding system implementation and following up on various factors that are input by operators regarding information needs. system-generated finances.